Dynamic and balanced regulation of the thrABC operon gene for efficient synthesis of L-threonine - Hao, Ruxin; Wang, Sumeng; Jin, Xin; Yang, Xiaoya; Qi, Qingsheng; Liang, Quanfeng (Frontiers in Bioengineering and Biotechnology, 2023)
L-threonine is an essential amino acid used widely in food, cosmetics, animal feed and medicine. The thrABC operon plays an important role in regulating the biosynthesis of L-theronine. In this work, we systematically analyzed the effects of separating thrAB and thrC in different proportions on strain growth and L-threonine production in Escherichia coli firstly. The results showed that higher expression of thrC than thrAB enhanced cell growth and L-threonine production; however, L-threonine production decreased when the thrC proportion was too high. The highest L-threonine production was achieved when the expression intensity ratio of thrAB to thrC was 3:5. Secondly, a stationary phase promoter was also used to dynamically regulate the expression of engineered thrABC. This strategy improved cell growth and shortened the fermentation period from 36 to 24 h. Finally, the acetate metabolic overflow was reduced by deleting the ptsG gene, leading to a further increase in L-threonine production. With these efforts, the final strain P2.1-2901ΔptsG reached 40.06 g/L at 60 h fermentation, which was 96.85% higher than the initial control strain TH and the highest reported titer in shake flasks. The maximum L-threonine yield and productivity was obtained in reported fed-batch fermentation, and L-threonine production is close to the highest titer (127.30 g/L). In this work, the expression ratio of genes in the thrABC operon in E. coli was studied systematically, which provided a new approach to improve L-threonine production and its downstream products.